1984
DOI: 10.1073/pnas.81.1.243
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of malignant transformation in vitro by inhibitors of poly(ADP-ribose) synthesis.

Abstract: Malignant transformation in vitro of hamster embryo cells and mouse C3H lOT'/2 cells by x-rays, ultraviolet light, and chemical carcinogens was inhibited by benzamide and by 3-aminobenzamide at concentrations that are specific for inhibition of poly(ADP-ribose) formation. These compounds slow the ligation stage of repair of x-ray and alkylation damage but not of ultraviolet light damage. At high concentrations they also inhibited de novo synthesis of DNA purines and DNA methylation by S-adenosylmethionine. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 29 publications
3
36
1
Order By: Relevance
“…This finding has been extended by Borek et al (1984) (1) Cells are reported to possess both ADPribose dependent and -independent DNA repair pathways (Bohr & Klenow, 1981;Zwelling et al, 1982) and the independent pathway is suggested to be more rapid and error-prone than the dependent pathway. This may not be the case, however, in the putative independent pathway in all cell types.…”
Section: Adp-ribosylation and Neoplastic Transformationmentioning
confidence: 81%
See 2 more Smart Citations
“…This finding has been extended by Borek et al (1984) (1) Cells are reported to possess both ADPribose dependent and -independent DNA repair pathways (Bohr & Klenow, 1981;Zwelling et al, 1982) and the independent pathway is suggested to be more rapid and error-prone than the dependent pathway. This may not be the case, however, in the putative independent pathway in all cell types.…”
Section: Adp-ribosylation and Neoplastic Transformationmentioning
confidence: 81%
“…Borek et al (1984) have only recently shown that benzamide and 3-aminobenzamide inhibit both purine synthesis and methylation mediated by S-adenosylmethionine. The effects of these inhibitors on differentiation in intact cells may be due to glucose starvation, since Grunfeld & Shigenaga (1984) found that nicotinamide, benzamide and bromodeoxyuridine inhibit deoxyglucose uptake in differentiated 3T3-L1 fat cells, OK opossum kidney cells and UMR bone cells.…”
Section: Effects Of Adprt Inhibitors On Dna Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkylation of oxygen atoms of purines and pyrimidines of DNA has been suggested to be critical to mutagenesis and carcinogenesis (40) and a positive correlation has been found between tumorigenesis and the formation and persistence of the promutagenic lesion 06 alkylguanine in target tissues (12,(23)(24)(25)31,33 Ci/mmole) were supplied by New England Nuclear Corporation, (Boston, MA). Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Poly(ADP)-ribosylation (ADPR) of chromosomal proteins may represent a mechanism of regulation of gene expression by active oxygen because it is intimately related to the redox state of the cell, DNA strand breakage and chromatin conformation (Hollenberg and Ghani, 1982;Uchigata et al, 1982;Purnell et al, 1980;Mandel et al, 1982;Poirier et al, 1985). Evidence for a role of ADPR in DNA repair (Jacobson et al, 1983;Wielckens et al, 1983;Durkacz et al, 1980), cell differentiation (Althaus et al, 1982;Johnstone and Williams, 1982;Farzaneh et al, 1982) and malignant transformation (Kun et al, 1983;Borek et al, 1984) has been obtained. We now report that the potent mouse skin promoter phorbol-12-myristate-13-acetate (PMA), which produces a prooxidant state in several cell types (see Cerutti, 1985), increased poly(ADPR) levels via the intermediacy of active oxygen in mouse embryo fibroblasts C3H1OT1/2 and human fibroblasts 3229 (Singh et al, 1985a).…”
Section: Introductionmentioning
confidence: 99%